DEVELOPING CREATIVE AND TECHNOLOGICAL COMPETENCIES THROUGH BLENDED LEARNING APPROACHES - Sharipova Gulshoda Bahriddinovna (SCIENCE AND CULTURE: INNOVATIONS OF THE 21ST CENTURY, 2025)
Abstract: This article explores how blended learning approaches can foster students’ creative and technological competencies. By combining traditional classroom instruction with digital learning tools, blended learning provides a flexible, interactive, and engaging educational environment. The study highlights that integrating face-to-face activities with online platforms enhances students’ problem-solving, innovative thinking, and technological skills. Understanding the benefits of blended learning allows educators to design effective strategies that support creativity and technological development simultaneously.